Pengaruh Gamification dan Perceived Enjoyment Terhadap Repurchase Intention Pada Aplikasi Mobile Shopee di Kota Bandung - Rini Handayani; Maya Ardila (Global Leadership Organizational Research in Management, 2023)
This study aims to determine how much the influence of gamification and perceived enjoyment contributes to repurchase intention both partially and simultaneously on the Shopee mobile application. The research methods used in this study are descriptive methods and associative methods. In this study, the unit of analysis is individuals, namely users of the Shopee games feature in Bandung City who use the Shopee mobile application. The sample in this study was 97 respondents. Sampling with certain considerations or criteria is a sampling technique used in this study. The analysis method uses multiple linear regression analysis, in addition to testing the validity and reliability of the research instrument. The results of the study show that gamification has a partial effect on repurchase intention. Perceived enjoyment has a partial effect on repurchase intention. Gamification and perceived enjoyment simultaneously affect the repurchase intention on the Shopee mobile application.